Killip classification and glucose level in patients with acute myocardial infarction - Cheng, Hsien-Hung; Yen, Pai-Chun (The American journal of emergency medicine, 2010)
Killip classification is a valuable prognostic stratification for patients with acute myocardial infarction. Patients with high initial glucose levels also have adverse outcomes. We hypothesize that an increase in the Killip classification rank of patients with acute myocardial infarction might be associated with increase in initial glucose levels. In a retrospective cohort study, patients receiving percutaneous coronary angiography after an acute myocardial infarction were enrolled. Patients were accorded Killip classifications, and the data were compared using the χ 2 and 1-way analysis of variance tests. The study was conducted on 246 eligible subjects. Higher initial glucose levels were associated with higher rate of hospitalization within 1 year as well as mortality ( P < .05). Glucose levels among the 4 Killip classes were different ( P < .05). Patients ranked in the higher Killip classes had higher glucose levels than those ranked in the lower classes.